Determinants affecting internet addiction among international business students in UiTM Melaka City Campus / Fatin Nabilah Mohd Annuar - Mohd Annuar, Fatin Nabilah (Faculty of Business and Management, 2016)
This research aims to investigate the determinants affecting internet addiction among International Business students in UiTM Melaka City Campus. Nowadays, university students have used the Internet more than necessary. This habit affect academic performance to drop gradually with the increasing number of addicted users of the Internet. 58% of students faced from poor study habits. poor grades or failed school due to overuse of the Internet (Young, 2008). Therefore, this research is conducted to analyse the factors of Internet addiction which are depression, self control and interpersonal relationship. Addiction might be characterized as a procedure whereby a conduct, that can function both to produce pleasure and to provide relief from internal discomfort, is utilized in an example described by (1) irregular inability to control the behaviour (weakness) and (2) continuation of the conduct regardless of huge negative outcomes (unmanageability) (Goodman, 1990). Despite the goodness in internet, internet addiction issues has risen day by day. New issue has emerged; an increasing number of people are devoting excessive daily life hours on internet. (Shirinkam et al., 2016) Internet addiction has been delegated a mental issue and the issue has happen often as possible as number of patients who allude to psychtrist is rising. Multiple Regression is used to measure independent variables and the dependent variable through its strength of relationship. The data collected for this research paper through questionnaires that are distributed to the International Business students in UiTM Melaka City Campus.